Obesity parameters, physical activity, and physical fitness are correlated with serum dipeptidyl peptidase IV activity in a healthy population. Issue 5 (May 2018) - Sanz, B.; Larrinaga, G.; Fernandez-Atucha, A.; Gil, J.; Fraile-Bermudez, A.B.; Kortajarena, M.; Izagirre, A.; Martinez-Lage, P.; Irazusta, J.
Abstract: Objective: To determine whether obesity, physical fitness, and physical activity parameters are associated with the enzymatic activity of serum dipeptidyl peptidase IV (sDPPIV) in a sample of healthy women and men. Design and methods: We have correlated parameters of obesity, physical fitness, and physical activity with sDPPIV activity in 374 healthy subjects (age: 60.7 ± 6.9 years, body mass index: 26.1 ± 4.1 kg/m 2 ). Enzymatic activity was analyzed using spectrofluorimetry, body composition was assessed by impedanciometry, physical fitness data were obtained using the Senior Fitness Test, and physical activity data were collected by accelerometer. Pearson's partial correlation analysis was applied to determine the relationship between DPPIV activity and the rest of parameters and significantly correlated variables were introduced into linear regression models to predict DPPIV. Results: Serum DPPIV activity was negatively associated with obesity parameters such as body mass (r = −0.112), body mass index (BMI) (r = −0.147), waist circumference (r = −0.164), waist-to-hip ratio (−0.104), and percentage of fat mass (r = −0.185). Serum DPPIV activity was positively associated with cardiovascular fitness (r = 0.138), total amount of physical activity (r = 0.153), and time spent doing light exercise (r = 0.184). Regression models revealed sex differences in enzyme activity with overall activity higher in women than in men (β = 0.437, p < 0.001). Further, percent fat mass was an independent negative predictor of DPPIV activity (β = −0.184, p = 0.001). Serum DPPIV activity was positively predicted based on the amount of time spent doing light physical activity (β = 0.167, p = 0.001). Conclusion: Our results demonstrate that sDPPIV activity is positively associated with healthier parameters regarding fatness, fitness and physical activity.